2018
DOI: 10.1016/j.bjm.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Structure analysis of capsid protein of Porcine circovirus type 2 from pigs with systemic disease

Abstract: Economic losses with high mortality rate associated with Porcine circovirus type 2 (PCV2) is reported worldwide. PCV2 commercial vaccine was introduced in 2006 in U.S. and in 2008 in Brazil. Although PCV2 vaccines have been widely used, cases of PCV2 systemic disease have been reported in the last years. Eleven nursery or fattening pigs suffering from PCV2 systemic disease were selected from eight PCV2-vaccinated farms with historical records of PCV2 systemic disease in Southern Brazil. PCV2 genomes were ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 36 publications
(63 reference statements)
1
19
0
Order By: Relevance
“…While PCV2a vaccines have been demonstrated to generate some cross-protection from clinical PCV2, associated disease PCV2 viruses continue to evolve and instances of vaccine failures due to diverse PCV2 field virus challenge have been documented [ 30 ]. PCV2 vaccines generally do not provide sterilizing immunity [ 30 , 31 ] and historic single genotype PCV2 vaccines may not induce broad enough cross-protection to cover evolving field viruses [ 32 ]. In fact, traditional single genotype PCV2 vaccine use has contributed to the selection of emergent viruses [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While PCV2a vaccines have been demonstrated to generate some cross-protection from clinical PCV2, associated disease PCV2 viruses continue to evolve and instances of vaccine failures due to diverse PCV2 field virus challenge have been documented [ 30 ]. PCV2 vaccines generally do not provide sterilizing immunity [ 30 , 31 ] and historic single genotype PCV2 vaccines may not induce broad enough cross-protection to cover evolving field viruses [ 32 ]. In fact, traditional single genotype PCV2 vaccine use has contributed to the selection of emergent viruses [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, traditional single genotype PCV2 vaccine use has contributed to the selection of emergent viruses [ 33 ]. Emergent field viruses are especially different from vaccine strains in capsid epitopic regions [ 30 , 31 ]. Since the capsid is the immunodominant protein, shifts away from vaccine capsid epitopes may be contributing the vaccine failures.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the ORF3 protein, the detection of the capsid protein could be the variable result in PCV2-infected PBMCs via different antibodies, due to different PCV2 strains [49,74], conformational epitopes [75], or linear epitopes [49,76]. Previous studies indicated that antibody binding residues were often on the exterior of the capsid of PCV2 [48,49,70,74,77,78]. Although an epitope might be on the surface of the single capsid unit, it could bury in the VLP and be inaccessible to the antibody [79,80].…”
Section: Discussionmentioning
confidence: 99%
“…Genotypes a, b, and d are clinically relevant and most often associated with clinical PCV2-SD [ 3 , 10 ]. New virus genotypes including recombinants are continually being sequenced with changes focused primarily on the capsid (ORF2) genetic sequence [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even minor changes in the capsid amino acid sequence can alter the configuration of conformational epitopes and thereby affect PCV2 pathogenicity and immune differentiation including binding of neutralizing antibodies [ 13 , 14 ]. A growing dissimilarity in epitopes shared among evolving field strains and constant vaccine strains may be contributing to decreasing efficacy of PCV2a vaccines [ 3 , 12 , 15 17 ]. The hypotheses that minor variations in epitopic regions can lead to differences in immune recognition [ 11 , 15 17 ] and escape from the vaccine-induced immune response [ 11 , 18 ] have been raised previously.…”
Section: Introductionmentioning
confidence: 99%